2022
DOI: 10.3390/su142416951
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Green Technology Innovation with Corporate Social Responsibility, Firm Financial, and Environmental Performance: The Case of Chinese Manufacturing Industries

Abstract: This research aims to examine the relationship between corporate social responsibility (CSR), firm environmental performance (FEP), and firm financial performance (FFP), as well as how green technology innovation performs a mediating role in this relationship. The manufacturing firms listed on the Shenzhen Stock Exchanges were selected as the representative sample for the study, and data were gathered from 470 managers and directors of manufacturing firms using a simple random sampling technique. The response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 112 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…Moreover, sustainable innovation can also have a positive impact on a firm's non-financial performance measures, such as its brand reputation and employee satisfaction. For example, a study by Xu and colleagues [9] found that firms that implemented sustainable innovation practices had a stronger brand reputation and were more attractive to potential employees. In summary, innovation, particularly sustainable innovation, is critical to the performance of firms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sustainable innovation can also have a positive impact on a firm's non-financial performance measures, such as its brand reputation and employee satisfaction. For example, a study by Xu and colleagues [9] found that firms that implemented sustainable innovation practices had a stronger brand reputation and were more attractive to potential employees. In summary, innovation, particularly sustainable innovation, is critical to the performance of firms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The results fill the gap and contribute to the literature threefold. First, the present study responds to persistent calls for more studies on CSR in the developing economies context (Ali et al, 2020; Bahta et al, 2021; Xu et al, 2022) and the mechanism through which CSR affects a firm's financial outcomes (Pham & Tran, 2020; Yanez‐Araque et al, 2021). More specifically, this study found that CSR practices directly and through GI can enhance the financial performance of manufacturing companies in a developing economy like Pakistan.…”
Section: Introductionmentioning
confidence: 69%
“…Due to inconsistent findings, some scholars have also proposed that mediation mechanisms can better explain CSR and financial performance nexus (Bahta et al, 2021; Feng et al, 2022; Xu et al, 2022). This means that CSR needs underlying mechanisms to transfer its effect on performance outcomes, which is currently disregarded in most previous studies and can lead to biased conclusions (Ali et al, 2020; Kraus et al, 2020; Padilla‐Lozano & Collazzo, 2022; Úbeda‐García et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicate that if a firm's ESG performance increases, its innovation performance will improve. Firm innovation is, therefore, considered a crucial factor in ensuring sustainability performance, as it also mediates the effect of ESG performance on firm performance [136] and other corporate issues [11]. Through innovation performance, the firm can develop products and sustainable manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…These literature works further evidenced that innovation influences ESG practices as well as sustainability, and the impact of ESG on some crucial corporate issues was found to be mediated by innovation. Chouaibi, Chouaibi [11] and Xu, Imran [136] identified mediating role of green innovation on ESG and financial performance. Ge, Xiao [137] demonstrated that innovation input mediates the relationship between ESG and the high-quality development of Chinese enterprises.…”
Section: The Mediating Role Of Innovation On the Relationship Between...mentioning
confidence: 99%